Academic libraries of the Siberian and Far Eastern region in the context of science development: past and present - E. B. Artemyeva; N. I. Podkorytova (Библиосфера, 2014)
The stages of the academic libraries formation in Siberia and the Far East since 1924, the time of appearance of the first scientific institution library, to 2014 were represented. The history of the centralized library systems (CBS) formation of the Siberian and Far Eastern Branches of the Academy of Sciences of the USSR (Russian Academy of Sciences) in the context of science development was reconstructed. Problems of libraries functioning arisen under conditions of science reform in connection with the adoption of the Federal Law № 253-FZ «On the Russian Academy of Sciences, reorganization of the state academies of sciences and amending certain legislative acts of the Russian Federation» (2013) and the Presidential Decree № 735 «On the Federal Agency of research organizations» (2013) were marked. Academic libraries play a leading role in scientific communication: acting as information centers extend the field of researcher information activity. Currently, the system of subordination of research institutions of the Russian Academy of Sciences and the algorithm of their funding are changed, that can adversely affect the performance of academic libraries operating under CBS frames. First of all, it will reflect on the document-information base, the quality of which depends largely on the capacity of its accession and development. Changing the model of economic-financial relations primarily will destroy the technology of centralized acquisition of library collections, which negatively affect science information support. From the authors’ point of view, CBS parted into autonomous libraries of research institutions will cease to exist as a single resource-forming center, coordinating and organizing information support of fundamental and applied research in Siberia and the Far East. Transformations will take place in the system of methodical management of libraries, which have successfully implemented by the central libraries of CBS on all directions of their activity. The algorithm of joint libraries actions promoting their effective development may be changed. Academic libraries need to find ways out of this situation in order to continue to fulfill their mission (information support of science, preservation of historical-cultural heritage and passing it to future generations).